(untitled) (Czech Journal of International Relations, 2000)
The Russian Federation is still in the stage of carrying out an uncontrolled search for a new social-economic model. It is shifting to an increasing extent into a development that finds it difficult to acquire a specific style. The fact is that the breakup of the worldwide bipolarity still traumatizes Russian society at all its levels. This is reflected in the style of running society and the state and strongly influences the international security climate. A dilemma arises where Russia is unable to survive without massive financial aid from the democratic West while at the same time doing its utmost to maintain its global position of power. The Concept of the national security of the Russian Federation, an official public document, approved by the President on 10 January 2000, consists of a system of views on safeguarding the security of the population, society and the state against external and internal threats in all spheres of life. It indicates the most significant trends in the state policy of the Russian Federation. It is its fundamental security document and simultaneously the directive of the President for the Federal Parliament, the Federal government, the Security Council of the state and the federal executive bodies. The concept is divided into four sets of problems: Russia within the world community, its national interests, threats to national security and safeguarding national security. The Military doctrine of the Russian Federation, as formulated in the draft, is a document about doctrinal views which have been drawn up for the current transitional period as a military Concept of the national security of the Russian Federation. Its principles rest, above all, on the restored power potential of Russia, whose capacity is increased by endeavours to establish close ties and interconnection with coordinated forces within the CIS. It is not confined merely to sections of the armed forces, but its substantial feature is the military organization of the state as a system which embraces the management bodies, methods of safeguarding military security, Russia’s defence forces, their construction und preparation, military strategic principles, their deployment and tasks as well as military economic principles. It is divided into three parts: Principles of military policy, Military strategic principles and Military economic principles.